The Energiewende – Germany’s gamble - Buchan, D (Oxford Institute for Energy Studies, 2012)
Germany has set itself a huge challenge in trying to move away from fossil fuels and abandon nuclear power, while remaining a major industrial power. This challenge to create an Energiewende – an energy turnaround or transformation – has ambitious targets. David Buchan argues that Germany is on track to meet only one of its three main targets (a one-third renewable share of electricity by 2020), and that the country will fail to reach the second target (to cut energy consumption by a fifth by 2020), and that this failure will make attainment of the third goal (emission reduction) harder. In a broader sense, the gamble may still come off, provided future gains in renewable technology and jobs can be achieved with lower subsidy costs. No other country can tap such technical expertise from industry or such bottom-up activism from municipal companies and citizens’ cooperatives in support of low-carbon energy.